Rankov's Clinic or Treatment of Nothingness and Bleakness - Machala, Lubomír (Bohemica Olomucensia, 2024)
The article informs about the complex of Slovak literary awards Panta Rhei Awards and especially about Pavol Rankov's prose The Clinic, which won the PRA Literary Academy Award in 2023. After a brief introduction of the author and a recapitulation of his work to date, an interpretative analysis follows, emphasizing that this is a model prose, precise in partial details, but basically resigned to soul-searching verisimilitude, convincing motivation of the characters' actions or authenticity in depicting the setting. The story of an individual trying in vain to get into the care of a renowned expert is a conscious variation on the works of world-famous authors (Kafka, Beckett, Orwell, etc.), emphasising the futility and futility of human striving and effort.
Keywords: Slovak literature; Panta Rhei Awards; Pavol Rankov; model prose; futility of human endeavour